Effective Sonosensitizer Delivery by Redox Sensitive Nanoparticles for Prostate Cancer Sonodynamic Therapy via Amplifying Oxidative Stress and Peroxidation. Issue 23 (30th September 2022) - Tong, Tongyu; Lei, Hanqi; Zhang, Shiqiang; Jiang, Donggen; Guan, Yupeng; Xing, Chengyuan; Chen, Huikun; Yang, Xiangwei; Kang, Yang; Pang, Jun
Abstract: Sonodynamic therapy (SDT), a novel noninvasive therapeutic modality, provides many noteworthy benefits by generating reactive oxygen species (ROS). However, water‐insoluble sonosensitizer delivery strategies have continuously underperformed because of unavoidable toxicity and a short circulation time. In this study, l ‐cystine derivative‐based biocompatible nanoparticles (NPs) that can be used in SDT and induce limited cytotoxicity are designed and synthesized. After ultrasonic (US) irradiation, these sonosensitizer‐loaded NPs show highly efficient sonodynamic performance that leads to cytotoxic ROS production. The ability to stop and start ROS generation induced by US irradiation enables accurate temporal and spatial control. In vivo and in vitro experiments are systematically performed to investigate the effects of this system on tumors, and the results indicate remarkable tumor suppression via markedly high persistent oxidative stress that induces peroxidation and endoplasmic reticulum stress. Thus, this novel temporally and spatially controllable ROS generation platform offers a safe and effective theranostic strategy for prostate cancer treatment. Abstract : This article highlights effective sonosensitizer delivery for sonodynamic therapeutic strategy. After ultrasonic irradiation, this strategy amplifies not only intracellular oxidative stress but also activate endoplasmic reticulum stress, ultimately boosting efficient antitumor effects.